Effect of preparation convergence on retention of multiple unit restorations - An in vitrostudy - Dileep Nag Vinnakota (Wolters Kluwer Medknow Publications, 2015)
Background and Aim: Convergence angle (CA) is one of the major determinant factors in the retention of single as well as multiple units. Hence, the aim of the present study was to determine the effect of preparation convergence on the retention of multiple unit restorations. Materials and Methods: Nickel-chromium alloy single crowns as well as three, six and nine multiple unit fixed partial dentures (FPDs) were casted for standardized milled dies that simulate canine, premolar and molar teeth machined with two different degrees of convergence, 12 (n = 55) and 20 (n = 55). The dies were threaded on rectangular metal platforms with the help of retainer shaft in the proper position to model either single or multiple preparations. The casted crowns and FPDs were cemented and retention tested by securing the units in an Instron universal testing machine. The tabulated values were analyzed statistically using Mann-Whitney test. Results: Single and multiple units with 12° CA needed greater force to dislodge compared to 20°, but this difference was not statistically significant for single units of premolar (P > 0.05). Irrespective of the angle, there was a simultaneous statistically significant increase in retention as the number of units increased in FPDs, except for the difference between 3 and 6 units in 20° group (P > 0.05). Conclusion: This study highlights the importance of emphasizing on CA, during canine and molar preparation for single units as well as preparation of canines for 6 units FPDs.